(untitled) - Bott, Robert (Edmonton, 1983)
Contents: The soft approach; The soft results; The soft strategy...
Keywords: Energy policy,Renewable energy sources,Năng lượng tái sinh,Chính sách năng lượng; Canada,Canada,Canada,Canada